In cold blood: Observational descriptive review of Eastern Massasauga rattlesnake bites reported to a single poison center over time. (30th January 2022) - Jacobs, Elizabeth; King, Andrew Marshall; Vohra, Varun
Abstract: The Eastern Massasauga rattlesnake ( Sistrurus catenatus catenatus ) is a pit viper indigenous to the Great Lakes region and the only venomous snake native to Michigan. It is small-to-medium, thick-bodied with dark brown, bow-tie shaped blotches. Its behavior is described as reclusive and docile and it prefers damp habitats. The venom of the Eastern Massasauga is primarily cytotoxic and hemotoxic. Previous literature describes severe coagulopathies following Eastern Massasauga envenomings, with some resulting in death. The objective of this study was to characterize Eastern Massasauga envenomings in humans reported to the Michigan Poison & Drug Information Center from 2003 to 2020, including a description of clinical manifestations, incidence and characterization of coagulopathies, and medical outcome severities. This was a retrospective review of Eastern Massasauga snakebites reported to our state poison center over time. Coagulopathies were classified according to previous toxicological snakebite literature. The degree of envenoming was scored using an institutional guideline, representing a modified version of validated snakebite severity score system. Our longitudinal review demonstrated Eastern Massasauga bites led to clinically significant toxicity, including persistent, recurrent, and late coagulopathies, though with low incidence of bleeding events. Cases typically resolved with use of antivenom. This, to our knowledge, is the largest descriptive case series characterizing Eastern Massasauga snakebites. Highlights: Characterizing the epidemiology of Eastern Massasauga rattlesnake envenomings. Describing the clinical toxicity, including coagulopathies, of Eastern Massasauga rattlesnakebites. Clinically significant toxicity, including coagulopathies, with low incidence of bleeding. Largest descriptive case series of Eastern Massasauga rattlesnakebites in humans.